Zooplancton abundance and species diversity in two lakes with different trophic states (Corrientes, Argentina) - Frutos, Santa Margarita (2009)
Aim: In this study, we compare the composition and abundance of zooplankton community between a lake affected by the domestic sewage and in an unaffected lake. We also identified the environmental variables associated with the variation in the most abundant populations and the rotifer species that are indicators of trophic state; Methods: Seventeen zooplankton samples (50 L per sample) were filtered through a plankton net (53 μm) in the limnetic zone of each site. Non periodic sampling was carried out between April/92 and March/08, during years with different rainfall regime to include the inter-annual variability; Results: Peaks of zooplankton abundance in the eutrophic lake were registered in spring and summer during eutrophication episodes in rainy years. This pattern was not found in the mesotrophic lake. A total of 50 species were registered in the eutrophic lake and 45 species in the mesotrophic lake, with a similarity of 0.71. Species richness was significantly greater in the samples from mesotrophic lake than in those from eutrophic lake. There was no significant difference between the specific diversity of the two lakes. Rotifera was the most abundant group in all samplings in both lakes. The Detrended Correspondence Analysis (DCA) scores indicate that the abundance of Keratella tecta, Filinia spp., K. Americana, Trichocerca similis and Brachionus havanaensis was related to eutrophication, whereas the abundance of Polyarthra dolichoptera, Keratella cochlearis, Conochilus spp., Brachionus spp. and Trichocerca spp. was related to mesotrophic conditions. The changes in the abundance of the dominant taxa were related to pH and water transparency; Conclusions: Our results indicate that the species richness and the relative abundance of dominant species are better indicators of eutrophic degree than total abundance and specific diversity. K. tecta can be considered a good indicator of eutrophic state of the lakes when its density exceeds 50% of total zooplankton abundance.